Tailoring Silicon-Based LGPS-Type Solid Electrolytes for All-Solid-State Lithium Batteries - Yang, Jingui; Justus Liebig University Giessen (My University, 2026)
All-solid-state batteries (ASSBs) are regarded as a promising next-generation energy-storage technology, but their practical implementation critically depends on suitable solid electrolytes (SEs). Among the various candidates, tetragonal Li10GeP2S12 (LGPS) and its derivatives exhibit some of the highest ionic conductivities reported so far. In particular, Si-based LGPS-type SEs have attracted considerable attention because of the low cost and high abundance of Si, together with their intrinsically fast Li-ion transport properties. However, the synthesis of this class of materials is complicated by complex structural polymorphism, the presence of side phases, and the sensitivity of ionic conductivity to synthesis conditions, microstructure and phase composition. This dissertation therefore focuses on investigating phase-transition mechanisms, structural relationships, and electrochemical properties of Si-based LGPS-type SEs. Operando high-temperature synchrotron X-ray diffraction and total scattering were employed to directly monitor the crystallization and phase-transition processes of Li10.5−xSi1.5P1.5S12−xIx (x = 0, 0.2, 0.4) across different length scales. These experiments clarified the thermodynamic stability relationship and kinetic competition between the highly conductive tetragonal phase and the poorly conductive orthorhombic phase, while also revealing the pronounced influence of microstructure on the phase-transition kinetics. On this basis, the role of LiI additives in promoting tetragonal-phase formation was systematically investigated. The results showed that, by tuning the iodine content and solid-state synthesis conditions, glass-ceramic SEs containing a nanocrystalline tetragonal phase can be obtained, combining high ionic conductivity with soft mechanical properties thus enabling improved chemo-mechanical stability during ASSB cycling. In ASSBs employing Ni-rich layered oxide cathode active materials, the glass-ceramic SEs outperformed both the amorphous and highly crystalline counterparts, demonstrating a more favorable balance among ionic conductivity, mechanical compliance, and interfacial stability. In all-solid-state lithium–sulfur batteries (ASSLSBs), iodine-containing Si-based LGPS-type SEs enabled exceptionally fast sulfur-conversion kinetics and excellent rate capability. This behavior originates from the synergistic interplay between the nanosized Si-based LGPS phase and an iodine-rich amorphous side phase. Such a dual phase composition not only provides efficient ion-transport pathways but also enables iodine as a fast redox mediator during cell charging, thereby markedly enhancing Li2S/S conversion kinetics. Overall, this dissertation advances the understanding of structural polymorphism in LGPS-type SEs and demonstrates that engineering synthesis pathways via LiI-assisted control is an effective strategy for optimizing this class of SEs. The experimental results further show that exploiting the synergistic interplay of multiple phase SEs represents a promising route for further optimization and thus advancing the practical realization of ASSBs.
Keywords: Solid-state batteries; LGPS-type solid electrolytes; Lithium-sulfur batteries; Redox-active catholytes; Lithium iodide additive; ddc:540; ddc:333.7